Trust as a Mechanism of Role-Dependent Regulation in Acrobatic Pairs - Maksymova, Yuliya; Voronova, Valentyna; Maksymov, Stanislav; Denysenko, Vladyslava; Kolesnik, Iryna (Physical Education Theory and Methodology, 2026)
Objectives. This study aimed to examine how cognitive and affective trust are organized within acrobatic pairs depending on compatibility type and partner role. It was hypothesized that trust organization varies across compatibility configurations and partner roles, and that the balance between cognitive and affective trust reflects distinct mechanisms of interaction regulation associated with responsibility distribution and regulatory tension within the dyadic system. Materials and Methods. The study involved 25 acrobatic pairs (N = 50 athletes) aged 11–16 years competing in acrobatic gymnastics at the stage of preliminary basic training. Compatibility types were determined according to a typology of acrobatic pair compatibility previously developed by the authors. The typology integrates indicators of technical execution reliability, postural and phase coordination, and emotional–expressive coherence. Interpersonal trust was assessed using an adapted version of Daniel J. McAllister’s Affect- and Cognition-Based Trust Scale. Nonparametric statistical procedures were applied, including Kruskal–Wallis tests, Mann–Whitney U tests, and Dwass–Steel–Critchlow–Fligner post-hoc comparisons. Results. The findings revealed generally high levels of interpersonal trust between partners. No statistically significant differences between partner roles were identified. However, the structure of trust organization differed across compatibility types. Functionally oriented pairs demonstrated relatively higher cognitive trust, whereas expressively oriented pairs exhibited relatively higher affective trust. Complex synergy pairs showed consistently high levels of both trust components and demonstrated the highest values on the trust balance index, indicating a more integrated mechanism of interaction regulation. Conclusions. Trust in acrobatic pairs functions not only as an individual psychological characteristic but also as a mechanism regulating interaction within a functionally asymmetric partnership. Variations in the balance between cognitive and affective trust reflect different coordination mechanisms associated with the distribution of responsibility, emotional synchronization, and interaction stability in acrobatic pairs.